HUBUNGAN PENGETAHUAN TERHADAP KEPATUHAN KONSUMSI TABLET TAMBAH DARAH (TTD) PADA REMAJA PUTRI DI MTs NU NEGARABATIN KOTAAGUNG BARAT KABUPATEN TANGGAMUS: The Relationship Between Knowledge and Compliance with Iron Supplement Tablet (TTD) Consumption in Adolescent Girls at MTS NU Negarabatin, West Kotaagung, Tanggamus Regency - Anggriani, Yunita; Komalasari; Ifayanti, Hikmah; Adawiyah, Rabiatul (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2025)
The prevalence of anemia according to the World Health Organization (WHO) in 2022, reached 50-65% worldwide, in Indonesia adolescent girls experienced anemia 18% in 2023, Lampung Province showed adolescents experiencing anemia 63% in 2023, in Tanggamus district as much as 8.7% and West Kotaagung District by 4.9% in 2023. One of the causes of anemia is iron deficiency, this can be prevented by giving blood supplement tablets in accordance. The dose given is one tablet every week. The purpose of this study was to determine the correlation between knowledge and adherence to the consumption of blood supplement tablets in adolescent girls at MTs NU Negarabatin West Kotaagung, Tanggamus District. The research method used was quantitative research with a cross-sectional approach. The research was conducted at MTs NU Negarabatin. The population of this study were all adolescent girls totaling 60 people. The sample technique used was total sampling. Data collection using a questionnaire that has been tested for validity and reliability. Data analysis was univariate and bivariate using Fisher Exact Test. The results showed that the knowledge of adolescent girls was mostly low, namely 36 adolescent girls (60.0%). Adherence to the consumption of blood supplement tablets in adolescent girls is not compliant, which amounted to 58 adolescent girls (96.7%). The Fisher Exact Test results obtained p-value = 0.156, so it was concluded that there was no correlation between knowledge and compliance with the consumption of blood supplement tablets at MTs NU Negarabatin. It is expected for teachers to provide support and for health workers to further increase socialization and counseling to adolescent girls about anemia and the importance of consuming blood supplement tablets